2010
DOI: 10.1248/jhs.56.462
|View full text |Cite
|
Sign up to set email alerts
|

Prazosin Stimulates the Release of Hepatic Triacylglycerole Lipase Caused from Primary-culture Rat Hepatocytes

Abstract: Prazosin is an alpha 1 adrenoceptor antagonist, and it is used as an antihypertensive agent. The effects of prazosin on the activity of hepatic triacylglycerole lipase (HTGL) are not fully understood. In this study, we demonstrated that prazosin stimulates the release of HTGL activity from primary cultures of rat hepatocytes in a time-and dose-dependent manner. U-73122, a phopholipase C (PLC) inhibitor, suppresses prazosin's stimulation of the release of HTGL activity. Moreover, prazosin stimulated the increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…12) In this study, we investigated whether this prazosinstimulated HTGL release was due to a mechanism involving an increase in intracellular cAMP levels. We found that prazosin-stimulated HTGL release was markedly suppressed by the adenylate cyclase (AC) inhibitors 2′,5′-dideoxyadenosine (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…12) In this study, we investigated whether this prazosinstimulated HTGL release was due to a mechanism involving an increase in intracellular cAMP levels. We found that prazosin-stimulated HTGL release was markedly suppressed by the adenylate cyclase (AC) inhibitors 2′,5′-dideoxyadenosine (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In a previous study, we investigated the release of HTGL from rat hepatocytes after stimulation with prazosin. 12) It was considered that PLC activation played an important role in HTGL release. However, elucidating the involvement of other protein kinases is currently in progress.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation